Waste management: bio-fuel recovery from palm oil mill effluent (POME) - Moh, Ivy Heng Shi (Universiti Malaysia Sarawak (UNIMAS), 2013)
The main objective of this study is to produce biofuel (namely biodiesel) from palm oil mill effluent (POME), which is the main waste generated from the oil palm industry. POME is generated from the production of oil palm, in which every two tonne of fresh fruit bunch (FFB) of palm fruit can produce one tonne of PO ME Due to large amount of PO ME is being produced daily, the discharge of treated POME is being produced daily, the discharge of treated POME to receiving water bodies definitely cause serious pollution to the received water bodies. Indeed, literatures show that the oil content in POME can be converted to biodiesel. Therefore, in this research, the biodiesel will be produced from POME through simplified-step transesterification of POME using methoxide solution In order to give a simple, low cost and can be carried out in short durations method to recover the useful components in POME. Pre-treatment of POME was carried out before transesterification process to remove the unwanted solids. After transesterification, the biodiesel produced was purified using water to remove the unwanted chemicals and also dry with drying agent. FTIR analysis was used to confirm the products are biodiesel. Biodiesel that was produced by using 2.5% (wit) sodium methoxide from desolidification POME had better quality.